Investigations on sheath blight of rice In Punjab - and G.S. RATTAN, KULDIP SINGH CHAHAL, S.S. SOKHI* (Indian Phytopathology, 2003)
Sheath blight reduced grain filling by 32.3 per cent in rice when diseased area of top three leaves was 54.3 per cent. When all leaves were infected, yield recorded was 18 glplant as compared to 35.9 glplant in the healthy control. On artificial inoculations of rice cultivars, maximum disease severity was recorded in PR 103 (97.0%) with a yield loss of 43.4%. Weeds and some other crops growing along the paddy fields were observed as hosts of Rhizoctonia solani. Propiconazole (0.1%), edifenphos (0.1%), iprodione (0.3%), carboxin (0.2%) and carbendazim (0.1%) effectively controlled sheath blight.